Subsidios a la producción y efectos derivados de la formación de una unión aduanera - Méndez, José; Méndez, Luciano (Estudios de Economía, 2016)
Using a three-country reciprocal dumping model, this paper analyses the effects of tariff unions on welfare taking the possibility of production subsidies into account. Production subsidies are found to prevent the deviation of trade. Results are also obtained suggesting that although universal free trade is the most efficient situation it is not an equilibrium situation, and that regional liberalization will therefore not lead to universal free trade.